Progress on Designing a Chemical Retinal Prosthesis - Wu, Jiajia; Rountree, Corey M.; Kare, Sai-Siva; Ramkumar, Pradeep Kumar; Finan, John D.; Troy, John B. (Frontiers in Cellular Neuroscience, 2022)
The last major review of progress towards a chemical retinal prosthesis was a decade ago. Many important advancements have been made since then with the aim of producing an implantable device for animal testing. We review that work here discussing the potential advantages a chemical retinal prosthesis may possess, the spatial and temporal resolutions it might provide, the materials from which an implant might be constructed, and its likely effectiveness in stimulating the retina in a natural fashion. Consideration is also given to implant biocompatibility, excitotoxicity of dispensed glutamate, and known changes to photoreceptor degenerate retinas.